Concept and demonstration of an intermediate band tandem device for solar energy conversion1. (23rd October 2015) - Sippel, Philipp; Heitz, Simon; Elagin, Mikaela; Semtsiv, Mykhaylo P.; Eichberger, Rainer; Masselink, W. Ted; Hannappel, Thomas; Schwarzburg, Klaus
Abstract: We have realized a tandem solar cell design that combines a pin‐junction with a photovoltaic intersubband absorber. This concept allows harvesting light in the visible range and the near‐ and mid‐infrared at the same time, and theoretically, energy conversion efficiencies beyond the Shockley–Queisser‐limit could be achieved. A test structure was grown, and the operation of this concept could be confirmed, in principal with an optical two‐beam experiment. The basic characteristics of the device can be explained with an equivalent circuit design that consists of three individual cells, and we find an obvious analogy to the concept of the intermediate band solar cell with noteworthy advantages at some points. Our results show, that for a working device it is crucial to adjust the properties of the photovoltaic intersubband absorber for optimal charge separating performance at the working point of the solar cell. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : We have realized a tandem solar cell design that combines a pin‐junction with a photovoltaic intersubband absorber. This new concept allows to harvest light in the visible range and the near‐ and mid‐infrared at the same time and could potentially exceed solar energy conversion efficiencies of single‐bandgap materials. A test structure was grown containing III–V semiconductor quantum wells, and proof‐of‐principle was provided with an optical two‐beam experiment.